The influence of image of satisfaction customer to loyalty visitors village tour Betung Berseri, Village Source Rahayu, District Rembang Muara Enim Regency - Daniel Sihombing (Institute of Computer Science (IOCS), 2023)
Village Tour Betung Berseri located in the Village Source Rahayu ,District Rembang Muara Enim Regency South Sumatra Province . Own various type Power pull potency tour nature and recreation . Study This aim For test the influence of Village Image Travel and satisfaction visitors to loyalty visitors to the village Tour Betung Berseri located in the Village Source Rahayu , District Rembang Muara Enim Regency Good in a manner Partial nor Simultaneous research design used in study is quantitative casual . subject in study This is visitors to the village Tour Betung Serial , meanwhile object in study This is image and satisfaction visitors to loyalty visitor. Method data collection used is survey method , which was analyzed use multiple linear regression . Research results in a manner Partial show that Influential Image Variable positive and significant to loyalty visitors to the village Tour Betung Glow Where results obtained Image 2.282 > t table 0.67703 and value significant 7.025 > from alpha 0.05. On Variables Satisfaction visitors influential positive and significant to loyalty visitors to the village Tour Betung Glow with results 3.465 > t table 0.67703 and value significant 4.643 > from alpha 0.05. Besides it's Image and satisfaction visitors in a manner simultaneous influential positive and significant to loyalty visitors with results study found calculated F value of 12,732 with table F values is 3.09 so calculated F value > F table or 12.732 > 3.09 and level significant 0.70 <0.05.